2021
DOI: 10.1021/acsomega.1c01865
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Cell Wall Permeability Model Generation Using Chemoinformatics and Machine Learning Approaches

Abstract: The drug-resistant strains of Mycobacterium tuberculosis (M.tb) are evolving at an alarming rate, and this indicates the urgent need for the development of novel antitubercular drugs. However, genetic mutations, complex cell wall system of M.tb, and influx−efflux transporter systems are the major permeability barriers that significantly affect the M.tb drugs activity. Thus, most of the small molecules are ineffective to arrest the M.tb cell growth, even though they are effective at the cellular level. To addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…As noted above, similar to the previous studies [ 60 , 63 ], the compounds that have shown activity in any of the selected target-based assays were classified as permeable if they were active in any of the selected cell-based assays; otherwise they were taken to be impermeable. To this end, the publicly available PubChem 2022 database [ 77 ] was used as the source of (Big) raw data (in particular, it included both the assays synchronized with ChEMBL [ 61 ] and a number of additional assays).…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…As noted above, similar to the previous studies [ 60 , 63 ], the compounds that have shown activity in any of the selected target-based assays were classified as permeable if they were active in any of the selected cell-based assays; otherwise they were taken to be impermeable. To this end, the publicly available PubChem 2022 database [ 77 ] was used as the source of (Big) raw data (in particular, it included both the assays synchronized with ChEMBL [ 61 ] and a number of additional assays).…”
Section: Resultsmentioning
confidence: 75%
“…As noted above, similar to the previous studies [ 60 , 63 ], the compounds that have shown activity in any of the selected target-based assays were classified as permeable if they were active in any of the selected cell-based assays, otherwise, they were taken to be impermeable. As the source of (Big) raw data, the publicly available PubChem 2022 database [ 77 ] was employed.…”
Section: Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…We consider this finding of high relevance since Mtb permeability is one the major concerns when developing potential antimycobacterial drugs. Nevertheless, bacterial cell permeability is a complex property that it is controlled by physiochemical, biological, and chemical processes such as stereochemistry, lipophilicity, saturation and unsaturation, flexibility, viscosity, fluidity, pressure, temperature and physiological conditions (Nagamani and Sastry, 2021). How these variables change to allow the release of MEVs is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed predictive QSAR models suggest the importance of molecular connectivity, lipophilicity, electrotopological states, and functional groups of a molecule in determining its Mtb cell wall permeability. Different machine learning models to predict the Mtb membrane permeability were compared [24]. In the study [25], a predictive in silico model of Mtb cell wall permeability applicable to diverse drugs and drug-like compounds was derived from the extensive Big Data-based dataset.…”
mentioning
confidence: 99%